Amanat Agung sebagai Tugas Misi: Apa dan Siapa yang Ditugaskan - Baginda Sitompul; Tomson Sihol Sianturi; Jefpri Sihombing; Riki Toni Situmeang; Dantoni Manalu (Jurnal Silih Asuh : Teologi dan Misi, 2024)
The Great Commission was the last message that gave by Jesus to His disciples before His ascension to heaven. It is an absolute command that must do by all believers who have faith in Christ. It also must be a cornerstone for evangelical activity. Goal of the great commission's activity is to share that salvation has provided in Jesus so since that is also God's grace and love it can be felt by everyone who give response and believe. To have a correct understanding so that capable to get the conclusion based on the truth, observation using exegetical method according to excavation from the original language could be support the discovery. The main purpose of Great Commission is "to make all the nations Christ's disciple." The process to make discipleship started by mission, followed by baptizing and teaching. The phrase of "to make all nations disciple" has meaning to make all nonJewish or people who unknown God, unbelievers, and gentiles, become Christ's followers. The Lord God willing to that all nations to be His disciples. Discipleship needs an obedience to produce multiplication from the devout of disciples themselves as well. Church or believers must realize to this mission (marturia) as the main task that must be done. l. Evangelism must be done immediately and become a lifestyle of all believers. Means that evangelism must be done anytime and anywhere. When believers don't do evangelism, then it proves that they don't care about the salvation of others. And when do not care about salvation of others, hence in this case church sinned. Sinned because of disobeying the Lord's commandment.